Open Access Publishing in the European Union: The Example of Scientific Works - Koutras, Nikos (2020)
Access to information resources and publicly-funded research outcomes have been considered in Europe during the last decade. Open access practice became part of the European institutions’ agenda since 2006 within the final report of the European Research Advisory Board. The Lisbon Treaty (2007) explicitly confirmed the European Union’s commitment to free circulation of scientific knowledge (Article 179 TFEU) and the dissemination of research results (Article 183 TFEU). In this regard, the Horizon 2020 program illustrates the importance of open access policy towards further dissemination of scientific information. The European Commission also introduced in July 2012 a scientific information package to empower the advantages of public investments in research (European Recommendation 2012/417/EU) which has been recently revisited (May 2018). This paper argues that open access practice has a potential to enhance copyright governance and related policies. The first part of the paper is aimed at a thorough conceptualization of open access practice. The second part discusses the emergence of open access at International and European level and responses from institutions, respectively. The third part argues about the lack of open access implementation in Europe with some examples from Member States. The paper concludes with recommendations as to how integration of open access in the European copyright law policy contributes to furthering access opportunities to scientific works.